Analysis of Interregional Development Disparities in Banten Province - Putri Aqidatul Fadhilah; Dedi Budiman Hakim; Sugeng Budiharsono (Yayasan Darussalam Bengkulu, 2026)
Background: Regional development disparities remain a persistent challenge in Indonesia's decentralization era. Banten Province, as one of the country's most industrialized regions, exhibits a dual economic structure where advanced industrial zones coexist with agrarian lagging areas. This study analyzes the level of economic development disparity among districts and cities in Banten Province during the 2015–2024 period. Method: This study employs a descriptive quantitative approach using secondary data from the Central Statistics Agency (BPS) of Banten Province. The data consist of Gross Regional Domestic Product (GRDP) per capita at constant prices and population figures for each of the eight regencies/cities in Banten Province from 2015 to 2024. The Williamson Index was calculated to measure the level of interregional development disparity. Results: The findings reveal that the level of development disparity in Banten Province is relatively high and stable throughout the observation period, with the Williamson Index ranging from 0.627 in 2017 and 2019 to 0.636 in 2024. Cilegon City is the largest contributor to regional disparities (Williamson Index 0.47–0.48), supported by its high GRDP per capita which increased from Rp145,551,706.92 in 2015 to Rp194,522,001.91 in 2024. Pandeglang and Lebak Regencies consistently exhibit the lowest per capita GRDP, indicating persistent economic lag. Tangerang City and South Tangerang City recorded the lowest index values (0.02–0.10). Conclusion: The persistent high disparity reflects a structural concentration of economic activity in northern Banten. From an Islamic economic perspective, this condition contradicts the principles of al-'adalah (distributive justice) and falah (holistic well-being). Policy recommendations include fiscal redistribution, infrastructure investment in lagging regions, and optimization of Islamic social finance instruments (zakat, waqf) to promote inclusive growth.